Student Adaptation at a Higher Education Institution - Kepalienė, Inga; Žygaitienė, Birutė (Technium Social Sciences Journal, 2025)
The analysis of student adaptation at a higher education institution focuses on the problems students most often face when adapting to a new academic environment, social and emotional challenges and changes in living conditions. The study examines student adaptation at a higher education institution, focusing on the experience of Vilniaus Kolegija. It identifies the key factors that contribute to successful student adaptation, including social networks, academic support and individual characteristics. The study also highlights the challenges that students face during the transition period.